Towards low carbon development: The role of forest city constructions in China - Lisha Liao (Elsevier, 2021)
With the proposal of carbon peaking and carbon neutrality targets, China has made great efforts to reduce carbon emissions. The latest and most competitive carbon emission data from Chen et al. (2020) and the time-varying difference-in-differences (DID) model is used to examine the role of forest city construction (FCC) in reducing carbon emissions. The results show that the FCC reduced CO2 by 1.71% in Chinese cities, which is approximately equivalent to 1.79 million tons. These results are supported by a variety of robustness tests. Mechanism analysis shows that FCC not only directly increased green spaces and vegetation carbon sequestrations, but also had indirect effects by deriving green development models in cities, such as green transportation, green innovation, and energy consumption reduction. Furthermore, regarding city heterogeneity, FCC was more effective in eastern and southern cities as well as cities with more populations and better economy. In the context of carbon neutrality, these findings are significant to Chinese cities on the road to low carbon development and provide the enlightenment for other developing countries to achieve carbon emission reduction.